Lights and shadows of educational technologies: Social Sciences teaching as a case study - Luna, Diego; Pineda-Alfonso, José Antonio (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The aim of this paper is to contribute to a better and deeper understanding of the phenomenon of technological integration in today’s schools. To this end, the methods of autoethnography and critical discourse analysis are used in a case study focused on the experience of one of the authors as a Social Sciences teacher in Secondary School. The system of categories constructed allows us to empirically confirm the apologetic nature of educational discourses outside the classroom, but also to identify a set of challenges, inconsistencies, and difficulties that have so far gone unnoticed in the scientific literature.